Path Analysis of Social Support as Determinant of Anxiety in People at Risk of Covid-19 during The Pandemic - Lilik Marifatul Azizah; Imam Zainuri; Siti Kotijah (Indonesian Journal of Community Health Nursing, 2021)
Introduction: Coronavirus disease 2019 (Covid-19) is an acute respiratory syndrome with a variety of specific symptoms that can lead to fatal death, causing public anxiety about contracting this disease and uncertainty of health status. The purpose of this study was to determine the path analysis of the effect of social support on anxiety for people at risk of Covid-19 during the pandemic.Method: The design was an explanatory study with a population of all Covid-19 People at Risk in Kemlagi District, Mojokerto Regency, with a sample of 150 respondents by random sampling. The exogenous variable was social support which is measured using the Social Support Questionnaire (SSQ). The endogenous variable was anxiety measured by the GAD-7 (Generalized Anxiety Disorder-7) questionnaire which consists of 7 questions about signs and symptoms of normal/appropriate affective, cognitive, and physical behavior. The analysis with Structural of Equation Model (SEM) with Partial Lease Square (PLS) approach with theory-based model development and path diagram development.Result: The level of anxiety of people at risk in facing the Covid-19 outbreak is directly affected by emotional support (path coefficient of 0.516 and statistical T value of 8.289), and information support about Covid-19 with a path coefficient of 0.286 and statistical T value of 3.868. Instrumental support has an indirect effect on anxiety (significance probability (P) 0.385> 0.05). The findings in this study are that social support (emotional and informational) can reduce the level of anxiety of people at risk of Covid-19 during the pandemic.Conclusion: When people are at risk of facing the Covid-19 outbreak, social support helps improve people's ability to the interpretation of stressors during the pandemic properly, and utilize the resources used in solving problems, and good coping efforts, so that the level of anxiety during the pandemic decreased.